The past, present and future state of missing persons investigations in Australia. Issue 6 (2nd November 2018) - Ward, Jodie
Abstract: The 2005 'Palmer Inquiry' highlighted the urgent need for the development of a national missing persons database, however a decade later Australia still does not have a national capability dedicated to missing persons identification. With an estimated 500 cases of unidentified human remains and 2000 long-term missing persons in Australia, there is still a pressing need for the establishment of a national identification program. I believe a DNA-led approach is essential for the effective and efficient identification of Australia's unknown and missing citizens. Despite DNA being used worldwide to identify large numbers of victims of war, genocide or mass disasters, the processing of DNA samples for routine missing persons investigations is under-addressed and under-resourced in Australia, resulting in current casework backlogs. The combination of technological advancements in DNA profiling, enhanced national databasing capabilities, publication of a national missing persons policy and international best practice guidelines, increasing community awareness of missing persons cases, and a passionate Churchill Fellow, is a recipe for successfully driving a national missing persons capability from concept to reality. However, success will be dependent on the provision of adequate government, policing and forensic resources, at a time when Australian law enforcement is challenged with competing operational priorities.